(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The term translation activity usually refers to the process of transferring written or oral texts into an equivalent text in another language. Generally, the purpose of translation is to create a copy of various types of texts, including religious, literary, scientific, and philosophical works, in another language, thereby making them accessible to a wider readership.